Website based learning student motivation and vocabulary mastery in EFL settings a systematic review - Dian Hardianti; Fitrawati Fitrawati (Indonesian Counselor Association (IKI), 2025)
This systematic review investigates the effects of website-based learning on student motivation and vocabulary mastery in English as a Foreign Language (EFL) contexts. Guided by the PRISMA 2020 framework, thirty-five empirical studies published between 2013 and 2024 were selected from major academic databases, including Scopus, Web of Science, ERIC, and Google Scholar. The review synthesizes evidence on how web-based platforms—such as learning management systems, interactive vocabulary websites, multimedia environments, and gamified tools—support motivational engagement and lexical development. The findings indicate that website-based learning consistently enhances learner motivation by promoting autonomy, reducing anxiety, and increasing enjoyment through interactive and gamified features. Flexible access, immediate feedback, and personalized learning pathways further contribute to sustained engagement. In terms of vocabulary mastery, web-based instruction significantly improves word recognition, recall, retention, and contextual usage. Platforms integrating multimedia input, spaced repetition, and contextualized tasks show the strongest effects on vocabulary acquisition. Despite its benefits, several challenges were identified, including unequal access to technology, limited digital literacy, and the risk of reduced teacher–student interaction. Nonetheless, the overall evidence suggests that website-based learning provides substantial advantages over traditional methods when supported by appropriate pedagogical design. This review concludes that integrating website-based instruction into EFL classrooms can meaningfully enhance motivation and vocabulary learning, while future research should explore long-term impacts and platform effectiveness across diverse learner populations.